PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM KASUS HUMAN TRAFFICKING YANG ADA DI UKRAINA TAHUN 2016-2019 - ", Anita; Waluyo, Tri Joko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study analyzes the role of the International Organization for Migration Anti-humanitarian case through the International Organization for Ukraine Migration's anti-trafficking plan Human trafficking in Ukraine from 2016 to 2019. The issue of human trafficking In terms of international security, humanity has become an important issue.In analyzing, this study uses qualitative with descriptive analysis model, The purpose of this study is to analyze the theoretical role of IOM in Ukraine using Clive Archer's theory of the international role of organizations. The conclusion then reveals that the increase in the number of victims identified in 2016 to 2019 was not due to a decrease in the role played by IOM in Ukraine, but to one of the main effects of the Ukraine and Russia conflict.Keywords: International Organization For Migration , Human Trafficking